Peran Guru dalam Meningkatkan Motivasi Belajar Siswa - Wahyuningsih Wahyuningsih; Ahmad Najihudin; Ivan Ilham Riyandi; Fani Laffanilah; Renaldi Ramadhan (Student Scientific Creativity Journal, 2024)
The role of teachers in increasing student learning motivation is one of the integral activities that must exist in learning activities. In addition to providing and transferring knowledge, teachers are also tasked with increasing children's motivation in learning. It is undeniable that student learning is very different from other people's, therefore it is important for teachers to always motivate students so that students always have a spirit of learning and are able to become outstanding students and can develop themselves optimally. The learning process will be successful if students are motivated to learn. Therefore, teachers need to grow students' learning motivation optimally. Teachers are required to be creative to motivate students to learn. Learning motivation is the meaning, value, and learning benefits of learning activities that are quite interesting for students to carry out learning activities.